Calculation of the Moments of the Cardinal B-Spline - Udovičić, Zlatko (Sarajevo Journal of Mathematics, 2024)
In this paper we describe five methods for the calculation of the moments \begin{equation*}\label{Momenti} \mathbb{M}_{n,m}=\int_{0}^{m}φ_{m}(t)t^{n}dt, n\in\mathbb{N}_{0}, \end{equation*} where weight function $φ_{m}(·)$ is the cardinal B-spline of order $m,m\in\mathbb{N}.$ 2000 Mathematics Subject Classification. 65D07, 41A15